THU0068 ANTI-CARBAMYLATED ANTIBODIES ARE ASSOCIATED WITH TOBACCO AND POOR OUTCOMES IN RHEUMATOID ARTHRITIS. (June 2019) - Castellanos-Moreira, Raul; Rodriguez-García, Sebastian C; Ruiz, Virginia; Camacho, Oscar; Ramirez, Julio; Cuervo, Andrea; Garcia-Moreno, Cristina; Morla, Rosa; Puerta, José Gomez; Cañete, Juan D.; Haro, Isabel; Sanmartí, Raimón
Abstract : Background: Anti-carbamylated protein antibodies (Anti-CarP) represent a novel autoantibody family present in sera of patients with rheumatoid arthritis (RA) with high specificity. Objectives: To analyse the prevalence of Anti-CarP in an established RA cohort and evaluate their association with the presence of other autoantibodies and disease activity and severity. Methods: Cross-sectional study. Presence of Anti-CarP was analyzed in a cohort of patients with established RA (n: 158) by a home-made ELISA test using fetal calf serum. We investigated the demographic, radiological and current and at disease onset clinical features. Rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA) status were also assessed. Results: Anti-CarP were positive in 46.2% of the patients in our cohort and in 15.1%, 19.2% and 9.1% of the patients negative for ACPA, RF and both respectively. Demographic and clinical features are shown in table 1 . The mean titer of ACPA (1361±1054 U/mL vs. 918 ± 1092 U/mL) and RF (258 ± 255 AU vs. 174 ± 205 AU) were significantly higher in Anti-CarP positive patients. No difference in symptoms at RA onset was observed. Current (24.7% vs. 11.8%) and previous (54.8% vs. 37.6%) smoking consumption were significantly associated with Anti-CarP antibodies. Anti-CarP positive patients presented a higher CRP values (1. 0±1.6 mg/dL vs. 0.5 ±0.8 mg/dL), swollen joint count (1.3±2.2 vs 0.7 ±1.8) and patient global health assessment VAS (34.8 ±21.5 mm vs. 26.4 ±17.1 mm); although no between-group differences in disease activity (DAS28, CDAI, SDAI and RAPID3) or demographic features were observed. Anti-CarP positive patients presented significant higher scores in Larsen index (23.6 ± 15.7 vs. 15.7 ± 12.6) and disability (HAQ-DI >1) (23.3% vs. 8.3%). Conclusion: Anti-CarP were present in approximately half of the RA cohort and were also detected in seronegative (RF and/or ACPA) patients. In our cohort, patients with Anti-CarP antibodies presented higher tobacco consumption and poorer disease outcomes. Disclosure of Interests: Raul Castellanos-Moreira Speakers bureau: For Lilly and Merk Sharp and Dohme, Sebastian C Rodriguez-García: None declared, Virginia Ruiz: None declared, Oscar Camacho: None declared, Julio Ramirez: None declared, Andrea Cuervo: None declared, Cristina Garcia-Moreno: None declared, Rosa Morla: None declared, José Gomez Puerta Speakers bureau: BMS, Pfizer, Amgen, Juan D. Cañete: None declared, Isabel Haro: None declared, Raimón Sanmartí Speakers bureau: PFIZER, SANOFI, LILLY, MSD, UCB, NOVARTIS, JANSSEN